Concurrence of sleep problems and distress: prevalence and determinants in parents of children with cancer. Issue 1 (31st December 2019) - Rensen, Niki; Steur, Lindsay M. H.; Schepers, Sasja A.; Merks, Johannes H. M.; Moll, Annette C.; Grootenhuis, Martha A.; Kaspers, Gertjan J. L.; van Litsenburg, Raphaële R. L.
ABSTRACT: Background : Parents of children with cancer are at risk for sleep problems. If these problems persist, an important perpetuating factor might be ongoing parental distress. Objective : The aim of this study is to assess the prevalence of sleep problems and the concurrence with distress in parents of children treated for cancer, and to identify predictors of this symptom clustering. Method : Parents completed the Medical Outcomes Study (MOS) Sleep Scale and Distress Thermometer for Parents (DT-P). Clinically relevant sleep problems were defined as a score >1SD above the norm and clinical distress as a thermometer score above the established cut-off of 4. Four parent categories were constructed: neither sleep problems nor distress; no distress but sleep problems; no sleep problems but distress; both sleep problems and distress. Predictive determinants (sociodemographic, medical, psychosocial) for each category were assessed with multilevel multinomial logistic regression. Results : Parents (202 mothers and 150 fathers) of 231 children with different cancers participated. Mean time since diagnosis was 3.3 ± 1.4 years (90% off-treatment). The prevalence of sleep problems was 37%. Fifty percent of parents reported neither sleep problems nor distress, 9% had only sleep problems, 13% only distress, and 28% reported both. Compared to parents without sleep problems or distress, parents who reported both were more likely to report parenting problems (OR 4.4, [2.2–9.1]), chronic illness (OR 2.8, [1.2–6.5]), insufficient social support (OR 3.7, [1.5–9.1]), pre-existent sleep problems (OR 6.2, [2.0–18.6]) and be female (OR 1.8, [1.1–4.2]). Conclusions : Sleep problems are common in parents of children treated for cancer, and occur mostly in the presence of clinical distress. Future research must show which interventions are most effective in this group: mainly targeted at sleep improvement or with prominent roles for stress management or trauma processing. HIGHLIGHTS: Pediatric cancer diagnoses are traumatic for parents and can precipitate insomnia. If insomnia persists, an important perpetuating factor might be ongoing distress. This study in 352 parents of children treated for cancer shows a high prevalence (37%) of sleep problems, in the majority of parents occurring in concurrence with clinical distress. Several predictors were identified. Future research should reveal which interventions are most effective: targeted at sleep improvement, or at stress management and trauma processing.